Effects of Hypothyroidism and Exogenous Thyroxine on Gastrointestinal Organs of Rat (Nigerian Journal of Physiological Sciences, 2021)
Summary: Thyroxine (T4) is important in gut development and maturation, and its use in treating hypothyroidism is becoming more popular. This study was conducted to evaluate the effect of thyroidectomy and thyroxine replacement on some gastrointestinal organs. Ten out of 20 thyroidectomised rats received 100pg/kgbw of T4 for five weeks to become euthyroid while the rest were left to become hypothyroid. Ten sham operated rats were made hyperthyroid by giving 100pg/kg.bw of T4 for five weeks, while the other ten sham operated rats served as control. 10mg/kg.bw intraperitoneal injection of ketamine was given as anesthesia for thyroidectomy and sham operation. At the end of the fifth week, the animals were sacrificed. Liver, stomach and small intestine were harvested and their morphological dimensions measured. Everted sacs were made from the small intestine for glucose transfer studies and slides for histomorphometry. There was no significant difference in the weights of the liver and stomach of the groups when compared with the control group. There was significant (p